ANALISIS PENGELOLAAN ATRAKSI WISATA KEBUN BINATANG SURABAYA (The Analysis of the Management of Tourism Attractions of Surabaya Zoo) - Yoyong Apriliana Sigit; Mas Roro Lilik Ekowanti; Dewi Casmiwati (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2018)
This research aims to determine how the management of tourism object Surabaya zoo which includes: Planning, Organizing, Directing and Supervision. Management of tourism objects is expected to perform good management considering this object tourism is an icon of Surabaya City. This research uses a good management theory according to George R.Terry (2010) which consists of planning, organizing directing and supervision. The method used in this research is descriptive qualitative method. This results of this research is that the management is well done enough and because of the nine indicators only six that have been good. These indicators are: goals, plans, jobs, employess, leadership, and relationship, while the other three indicators such as coordination is good enough. These are motivation and supervision are still lacking. This research suggests that the management of Surabaya Zoo to be better supervision and to be more improved again.